Excitation of Global Alfvén Waves by Low RF Power on TCABR. (March 2015) - Puglia, P G P; Elfimov, A G; Ruchko, L; Galvão, R M O; Guimarães-Filho, Z O; Ronchi, G; Fonseca, A M M; Kuznetsov, Yu K; Nascimento, I C; Reis, A P; de Sã, W P; Sanada, E K; et al.
Abstract: Recent results of Global Alfven wave (GAW) excited by external antenna and fed by low radio-frequency (RF) power (≤1kW) in tokamak TCABR are presented. The goal of this work is to develop a diagnostic tool based on the excitation of GAW using low power RF generators when the waves can be excited without perturbing the basic plasma parameters in TCABR. This method named MHD diagnostics has already been developed on other tokamaks for toroidicity induced Alfven eigenmodes as well for GAW. Two magnetic probes are used for measurements of the magnetic field perturbations in two regimes of excitation. In the first one, the fixed RF frequency is combined with gas-puffing induced density rise and relaxation (1-2)×10 13 /cm 3 in order to meet the GAW resonance, while in the second excitation method RF frequency sweeps 2-4 MHz are applied to the relatively stable plasma density. The plasma discharges are accompanied by saw-tooth (ST) oscillations registered by Soft-X Ray diagnostics that helps in an identification of the GAW resonances due to ST density oscillations. It is found that the fixed frequency GAW resonance appears during density rise, as well during slow density reducing after stop of gas puffing. The effective mass number Aeff =1.36 is found.